First Report of a Foodborne Salmonella enterica Serovar Gloucester (4:i:l,w) ST34 Strain Harboring blaCTX–M–55 and qnrS Genes Located in IS26-Mediated Composite Transposon - Li, Lili; Olsen, Rikke Heidemann; Song, Anhua; Xiao, Jian; Wang, Chong; Meng, Hecheng; Shi, Lei (Frontiers in Microbiology, 2021)
Extended-spectrum β-lactamases (ESBLs)-production and (fluoro)quinolone resistance amongst of Salmonella isolates imposes a public health threat. The objective of this study was the phenotypic and genotypic characterization of a ESBL-producing and nalidixic acid resistant Salmonella enterica serovar Gloucester isolate (serotype 4:i:l,w) of sequence type 34 (ST34) from ready-to-eat meat product in China. Whole genome short and long read sequencing (HiSeq and MinION) results showed that it contained blaCTX-M-55, qnrS1 and tetB, and aac(6')-Iaa genes, with blaCTX-M-55 and qnrS1 located in chromosomal IS26 mediated composite transposon (IS26-qnrS1-IS3-Tn3-orf-blaCTX-M-55-ISEcp1-IS26). The same genetic structure was found in a chromosome of Salmonella enterica subsp. enterica serovar Typhimurium strain and in several plasmids of Escherichia coli, indicating the IS26 mediated composite transposon in chromosome of S. Gloucester may originate from the plasmid of E. coli and possess the ability to disseminate to Salmonella and other bacterial species. Besides, the structural unit qnrS1-IS3-Tn3-orf- blaCTX-M-55 was also observed to be linked with ISKpn19 in chromosomal or plasmids of various bacteria species, highlighting the contribution of the insertion sequences (IS26 and ISKpn19) to the co-dissemination of blaCTX-M-55 and qnrS1. To our knowledge, this is the first description of chromosomal blaCTX-M-55 and qnrS in S. Gloucester from RTE meat product. Our work expands the host range and provides additional evidence of the co-transfer of blaCTX-M-55 and qnrS1 among different species of Salmonella through food chain.